LIMESTONE-MARL ALTERNATIONS: A WARM-WATER PHENOMENON? - Westphal H.; Munnecke A. (My University, 2003)
Ancient limestone-marl alternations are concentrated in settings analogous to loci of aragonite accumulation in the modern world. They typically occur on shelves in the tropical-subtropical climate belt, are far more abundant on passive continental margins than on active ones, and are rare in upwelling zones. In recent studies, aragonite was proposed to play an important role in differential diagenesis typical of most limestone-marl alternations. The coincidence of depositional settings of ancient limestone-marl alternations and modern aragonite accumulation is a strong case for this hypothesis. If confirmed, it could provide a valuable tool for broad-scale paleoenvironmental interpretations. An additional, different type of limestone-marl alternations resulted from the Cretaceous explosion in productivity of calcitic plankton: these pelagic ones are fundamentally different in their style of diagenesis.
Keywords: global maps; paleoenvironment; limestone-marl alternations; rhythmites; aragonite; differential diagenesis; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая